Non-pharmacological sleep interventions for youth with chronic health conditions: A critical review of the methodological quality of the evidence. (July 2013) - Brown, Cary A.; Kuo, Melissa; Phillips, Leah; Berry, Robyn; Tan, Maria
<x xml:space="preserve">Abstract</x> Purpose: Restorative sleep is clearly linked with well-being in youth with chronic health conditions. This review addresses the methodological quality of non-pharmacological sleep intervention (NPSI) research for youth with chronic health conditions. Method: The Guidelines for Critical Review (GCR) and the Effective Public Health Practice Project Quality Assessment Tool (EPHPP) were used in the review. Results: The search yielded 31 behavioural and 10 non-behavioural NPSI for review. Most studies had less than 10 participants. Autism spectrum disorders, attention deficit/hyperactivity disorders, down syndrome, intellectual disabilities, and visual impairments were the conditions that most studies focused upon. The global EPHPP scores indicated most reviewed studies were of weak quality. Only 7 studies were rated as moderate, none were strong. Studies rated as weak quality frequently had recruitment issues; non-blinded participants/parents and/or researchers; and used outcome measures without sound psychometric properties. Conclusions: Little conclusive evidence exists for NPSIs in this population. However, NPSIs are widely used and these preliminary studies demonstrate promising outcomes. There have not been any published reports of negative outcomes that would preclude application of the different NPSIs on a case-by-case basis guided by clinical judgement. These findings support the need for more rigorous, applied research.